Susceptibility of some dried medicinal plants to attack of Oryzaephilus surinamensis (L.) (Coleoptera Silvanidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The susceptibility of 24 dried medicinal plants commonly used in the food industry to attack of Oryzaephilus surinamensis (L.) was evaluated. The development of the beetle was observed on roots of Angelica archangelica, Rheum officinale and Valeriana officinalis, flowers of Citrus aurantium, flower heads of Crataegus oxyacantha, whole and sieved flower heads of Matricaria chamomilla, whole fruits of Foeniculum vulgare, whole berries of Juniperus communis, pressed fruits of Silybum marianum and leaves of Vitis vinifera.The highest mean number of adults, the shortest mean period of development and the highest mean index of susceptibility were observed on S. marianum. The lowest mean number of adults, the longest mean period of development and the lowest mean index of susceptibility were observed on M. chamomilla. O. surinamensis did not develop on 14 medicinal plants tested in the present study. The factors, that affected insect development on dried medicinal plants were various: quality and quantity of nutrition, presence of repellent, antifeedant, or with insecticidal action substances or the physical shape, dimension and state of the substrates.
Keywords: Oryzaephilus surinamensis; dried medicinal plants; insect development